The Balancing Act of Legal Investor Protection: A Literature Review on the Dual Role of Minority Shareholder and Creditor Safeguards in Corporate Investment Decisions - Ngadi Permana; Benardi Benardi; Mia Christy Patricia (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review examines the regulatory trade-off in legal investor protection, focusing on the dual role of minority shareholder and creditor protection in influencing firm investment decisions. The findings reveal that robust minority shareholder protection enhances equity market confidence and encourages long-term investments, while strong creditor rights reduce default risks but may limit managerial flexibility and risk-taking. The study highlights the contextual dynamics of these trade-offs across legal systems and market maturities, with developed markets benefiting from complementary protections and emerging markets facing prioritization challenges. This review underscores the importance of balanced legal frameworks tailored to specific economic and institutional contexts. Limitations include geographic bias, reliance on secondary data, and limited stakeholder focus. Future research should explore cross-country analyses and the role of technological advancements in corporate governance.